Narasi Spritual di Tiktok: Strategi Mikro-Dakwah dan Budaya Partisipatif Generasi Z di Indonesia - Muhamad Marzuki; Lalu Haqqulyakin Mulyawan; Muhammad Yani; Muhammad Athar; Daeng Sani Ferdiansyah (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2026)
The phenomenon of digital da’wah has undergone a significant transformation alongside the development of social media, particularly the TikTok platform, which is highly popular among Generation Z. Da’wah, which was previously hierarchical in nature, has shifted toward a more participatory model, where religious messages are conveyed through short narratives, humor, music, and engaging visuals. This study aims to describe the micro-da’wah strategies employed by young Muslim creators on TikTok and to analyze how participatory culture shapes the dynamics of disseminating Islamic values in the digital sphere. Using a descriptive qualitative approach based on digital ethnography, data were collected through online observation and content analysis of 100 videos from five Indonesian Muslim TikTok creators. The findings indicate that TikTok micro-da’wah presents four main narrative patterns: (1) reflective-spiritual narratives, (2) religious humor narratives, (3) motivational narratives, and (4) dialogical narratives. These contents reflect a new form of da’wah communication grounded in participatory culture, in which audiences actively contribute to shaping, interpreting, and spreading religious messages. This study concludes that TikTok has become an interactive space for da’wah that fosters a “digital ummah” and opens opportunities for innovative Islamic communication strategies in the era of participatory culture.